(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
The stimulus equivalence’s model has been applied to teach reading, using words as units of teaching. This study aimed to develop, implement and evaluate a reading program for two students with reading difficul-ties. The reading program uses sentences as unit of teaching and was implemented with a software named Mestre. Before the reading intervention, the students didn’t read sentences. After the intervention both obtained satisfactory performances in emergent relations; however they have presented different levels of reading generalization. They maintained the acquired repertoire 28 days later. The data show that after the intervention both participants had increased their reading sentences repertoire, reaching superior levels of performance compared with the previous one.